ANTIOXIDANT AND CYTOTOXIC ACTIVITY OF COMBINED EXTRACTS PREPARED USING FICUS RELIGIOSA AND FICUS BENGHALENSIS LEAVES AGAINST CERVICAL CANCER CELL LINE (HELA) - Kumaresan, Suriya; Ramasamy, Rema; Jayachandran, Philip Robinson (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Medicinal plants and herbs are used in combination in Ayurveda and folklore medicine as they exhibit good cytotoxic activity. In the present study, the antioxidant, phytochemical, and cell proliferation activity of the combined crude methanolic extract of Ficus religiosa and Ficus benghalensis leaves were investigated. Methods: Antioxidant activity was performed by 2, 2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) and hydrogen peroxide methods, and the presence of the phytochemicals was screened using the gas chromatography–mass spectrometry. The extract was further evaluated for its cell proliferation activity against cancer cells using the mitochondrial reduction assay. Antioxidant property of the extracts was measured using the DPPH, hydrogen peroxide, and ferric-reducing antioxidant power assay, respectively, using the UV spectrophotometer. Results: The combined extract exhibited strong antioxidant potential in DPPH assay by increase in the percentage of inhibition with the increase in concentration. Similarly, the IC50 value of the methanol extract in peroxidase scavenging activity was 49.85 μg/mL comparatively lower than the ascorbic acid used as standard. The phytochemical analysis of the methanol extract showed the presence of nine phytoconstituents, which exhibit antioxidant and anticancer property. Mitochondrial reduction assay performed to evaluate the cell proliferation activity of the combined leave extract showed that increase in the concentration of the extract decreased the cell proliferation in the HeLa cell line. Conclusion: The results of present study show a possible synergistic activity of leaves against human cervical cancer.